2000
DOI: 10.1136/gut.47.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Short course acid suppressive treatment for patients with functional dyspepsia: results depend on Helicobacter pylori status

Abstract: Background and aims-Treatment of functional dyspepsia with acid inhibitors is controversial and it is not known if the presence of Helicobacter pylori infection influences the response. Methods-After a complete diagnostic workup, 792 patients with functional dyspepsia unresponsive to one week of low dose antacid treatment were randomised to two weeks of treatment with placebo, ranitidine 150 mg, omeprazole 10 mg, or omeprazole 20 mg daily. Individual dyspeptic and other abdominal symptoms were evaluated before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 28 publications
(17 reference statements)
1
96
1
5
Order By: Relevance
“…30 Furthermore, the placebo response rates in patients with functional dyspepsia were 30-50%. [31][32][33] Because minimal change esophagitis patients who had symptoms including dyspepsia were included in the study, the placebo response rate was higher in our study than in previous studies on GERD. We believe that the high placebo response may have masked the differences in the efficacy of DA-9701 in patients with minimal change esophagitis.…”
contrasting
confidence: 48%
“…30 Furthermore, the placebo response rates in patients with functional dyspepsia were 30-50%. [31][32][33] Because minimal change esophagitis patients who had symptoms including dyspepsia were included in the study, the placebo response rate was higher in our study than in previous studies on GERD. We believe that the high placebo response may have masked the differences in the efficacy of DA-9701 in patients with minimal change esophagitis.…”
contrasting
confidence: 48%
“…Blum et al 21 reported that the efficacy of omeprazole was only evident in the H. pylori-positive subgroups. Thus, the anti-secretory effect of PPIs might be enhanced in H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although a standard treatment for FD has not been established, PPIs are widely used as the initial treatment choice in patients with EPS dominant FD. Several randomized controlled studies suggested that the efficacy of PPI therapy for FD is limited, and it may be confined to those patients who have co-existing EPS (Talley et al 1998;Blum et al 2000;Bolling-Sternevald et al 2002;Wong et al 2002;Peura et al 2004). One randomized control study compared PPI therapy to a placebo in FD patients with ulcer-like symptoms (van Rensburg et al 2008).…”
Section: Discussionmentioning
confidence: 99%